2018
DOI: 10.1002/ece3.3718
|View full text |Cite
|
Sign up to set email alerts
|

Timing of precipitation in an arid environment: Effects on population performance of a large herbivore

Abstract: Climate models predict that shifts in temperature and precipitation patterns are likely to occur across the globe. Changing climate will likely have strong effects on arid environments as a result of increased temperatures, increasing frequency and intensity of droughts, and less consistent pulses of rainfall. Therefore, understanding the link between patterns of precipitation, temperature, and population performance of species occupying these environments will continue to increase in importance as climatic sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…For our mostly arid region, we estimated, on average, 66.5 ± 10.11% reduction in current distribution of the target ungulates by 2070, which is similar to the estimate calculated for Marco polo sheep ( O. ammon polii ) in Tajikistan (65.6% loss; Salas, Valdez, Michel, & Boykin, 2018), but higher than those obtained for large mammals in generally less arid regions like the Tibetan Plateau (30%–55% loss; Luo et al., 2015), the African continent (18% loss; Thuiller et al., 2006), in tropical forests of Asia (37% loss; Deb, Phinn, Butt, & McAlpine, 2019) and temperate Europe (30% loss; Levinsky, Skov, Svenning, & Rahbek, 2007) indicating that climate change could have generally larger impacts on species in arid regions (Heffelfinger et al., 2018), such as central Iran. Within central Iran, however, we obtained different estimates of climate change impact on the future distribution of the ungulates, which may be related to varying rates of climate change across their habitats.…”
Section: Discussionmentioning
confidence: 99%
“…For our mostly arid region, we estimated, on average, 66.5 ± 10.11% reduction in current distribution of the target ungulates by 2070, which is similar to the estimate calculated for Marco polo sheep ( O. ammon polii ) in Tajikistan (65.6% loss; Salas, Valdez, Michel, & Boykin, 2018), but higher than those obtained for large mammals in generally less arid regions like the Tibetan Plateau (30%–55% loss; Luo et al., 2015), the African continent (18% loss; Thuiller et al., 2006), in tropical forests of Asia (37% loss; Deb, Phinn, Butt, & McAlpine, 2019) and temperate Europe (30% loss; Levinsky, Skov, Svenning, & Rahbek, 2007) indicating that climate change could have generally larger impacts on species in arid regions (Heffelfinger et al., 2018), such as central Iran. Within central Iran, however, we obtained different estimates of climate change impact on the future distribution of the ungulates, which may be related to varying rates of climate change across their habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that enhanced winter nutrition provided adult females that were less fit to successfully rear offspring with capital to invest in reproduction despite the limitations imposed by harsh winters. Heffelfinger et al (2018) demonstrated the importance of high-quality forage during midpregnancy (January-April) for mule deer occupying an arid environment. The timing of latewinter and early-spring precipitation facilitated rapid green-up in that system during crucial periods of fetal development (Marshal et al 2005, Heffelfinger et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Heffelfinger et al (2018) demonstrated the importance of high‐quality forage during mid‐pregnancy (January–April) for mule deer occupying an arid environment. The timing of late‐winter and early‐spring precipitation facilitated rapid green‐up in that system during crucial periods of fetal development (Marshal et al 2005, Heffelfinger et al 2018). Our findings also indicate the importance of nutritional resources during mid‐pregnancy in the Pacific Northwest.…”
Section: Discussionmentioning
confidence: 99%
“…Neonate survival can be influenced by maternal body condition with young born to females in good nutritional condition typically having higher birth mass and post‐parturition growth rates. Neonates that are heavier at birth typically have higher survival rates that those born lighter (Thorne et al , Fairbanks , Keech et al , Cook et al , Heffelfinger et al ). Several studies have reported a positive relationship between fall lamb:adult female ratios in desert bighorn sheep and rainfall during the previous winter period (Douglas and Leslie , Wehausen et al , Douglas , Wehausen , Longshore et al ), suggesting a link between rainfall during late gestation and early post‐parturition, and juvenile recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…During each year, we explored stage‐specific differences in survival rate using 7 a priori models of varying age intervals. Age intervals allow for survival rate estimation for specific biologically meaningful time intervals based on growth and development of young and have been examined with young grizzly bears ( Ursus arctos ; Schwartz et al ), elk ( Cervus canadensis ; Barber‐Meyer and Mech ), mule deer (Heffelfinger et al ), and white‐tailed deer ( Odocoileus virginianus ; Grovenburg et al ). We used stage‐specific intervals similar to those in Smith et al () in their survival estimation for Rocky Mountain bighorn sheep ( Ovis canadensis canadensis ) lambs in South Dakota, USA.…”
Section: Methodsmentioning
confidence: 99%